LEVEL OF ESTRADIOL 17-β SERUM AND OVARIAN FOLLICULARE DYNAMICS IN SHORT ESTROUS CYCLE OF BALI CATTLE - Airin, C.M; Putro, P.P.; Astuti, P.; Baliarti, E. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The aims of the research were to confirm the short estrous cycles and determine the blood level ofestradiol 17-β and ovarian follicukar dynamics in these cases. The research was conducted using sevenBali cattle, approximately 2 years of age, kept in healthy condition with normal estrous cycles.Observation of estrus symptoms was performed daily. Ovarian follicles was examined and measuredusing ultrasonography started at the estrus day. Blood samples were collected from jugular vein, bloodsample collection and ultrasonographical examination of the ovaries were performed daily in the sametime. Serum level of estradiol 17-β was performed using EIA. The short cycle estrus were observed in 4Bali cattle (n=7) among natural estrous cycle. They have only one wave ovarian follicular developmentwhereas the maximal size of ovarian follicles ovulation likes the normal cycle The duration of shortestrous cycle was 7-10 days with normal usual estrus behavior. The peak of blood serum level was107.77 ± 55.94 pg/ml when the diameter dominant follicle of short estrous cycle was reached 10.5 ±0.38 mm. It can be concluded that the short estrous cycles may occur in Bali cattle after puberty amongnormal cycles.